AYURVEDIC UNDERSTANDING OF BIOMECHANICAL DYSFUNCTION OF ANKLE JOINT WITH SPECIAL REFERENCE TO GULPHA MARMA ABHIGHATHA - T, *Aneesh.; Bedekar, Swati.S.; Kulkarni, B.G; Vinayak, Varun; Ravi, Visakh.S. (International Journal of Ayurveda and Pharma Research, 2016)
Marma sthana is the vital and most vulnerable point of the body. The prana or the life resides in it. Among the detailed and broad classification of Marma by Susruthacharya in his Sareerasthana, the Gulpha Marma is one among 20 Sandhi Marma (vital point related to joints) and one of the 8 Rujakara Marma according to its traumatic effect of pain. The Gulpha viz. ankle joint is located at the junction of Paada (foot) and Jankha (leg), the trauma in this region will leads to pain, restriction of movement, and limping. The ankle (talo-crural) joint is a uni-axial synovial joint, with primary movements of dorsi and plantar flexions. Ankle joint is one of the most frequently injured areas of the body since being the connecting link between stable leg bone and the mobile foot and subjected to great varieties of forces in walking, running, standing etc. If there is any trauma or injury at Gulpha Marma region that directly affect the (Gulpha Sandhi) ankle joint. The ligaments, tendons and bones have an important role in maintaining the stability of ankle joint and some clinical and pathological aspects of these are reviewed. Various traumas on ankle joint or Gulpha Marma leads to the biomechanical dysfunction of the joint.